The effect of relaxation technique on fatigue levels after stem cell transplant - Hedayat Jafari; Yadollah Janati; Jamshid Yazdani; Nasrin Bali; Somayeh Hassanpour (Wolters Kluwer Medknow Publications, 2018)
Background: Many patients undergoing hematopoietic stem cell transplant (HSCT) experience fatigue due to their disease process and its long period of treatment. Using nonpharmacological methods to help reduce their fatigue is a reasonable endeavor. The present study was conducted to investigate the effect of Benson's relaxation technique on fatigue levels in patients after HSCT. Materials and Methods: Thirty-seven patients were randomly selected to the intervention (n = 19) and control group (n = 18). In the intervention group, the participants performed Benson's relaxation exercises for 20 min twice per day over a period of 15 days. The data collection tools used included a demographic and medical information form and the Brief Fatigue Inventory, completed by both groups on three different occasions (upon admission and days 8 and 14 after the HSCT). The data obtained were analyzed in Statistical Package for the Social Sciences version-20 using statistical tests. Results: The results of the independent t-test showed no significant preintervention differences in fatigue levels between the two groups. On days 8 (t = 11.21, p < 0.001) and 14 after the transplant (t = 15.62, p < 0.001), a significant difference was observed in the mean level of fatigue between the two groups. Conclusions: These findings indicate that Benson's relaxation technique would improve fatigue in HSCT patients.